High Output Voltage Based Multiphase Step-Up DC-DC Converter Topology with Voltage Doubler Rectifiers - Amir Mahmood Soomro; Xu Lingyu; Shahnawaz Farhan Khahro; Liao Xiaozhong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
High Output Voltage Based Multiphase Step-Up DC-DC Converter topology with voltage doubler rectifiers is presented in this paper. High output voltage is obtained due to the series combination of voltage doubler rectifiers on the secondary side of high frequency transformers. This topology is useful in the application where the output voltage is greater than the input. The two loop control strategy has been developed in order to analyze the stable and effective working of the converter topology. Therefore the working mode analysis of the converter topology has been described in detail. The multiphase step-up DC-DC converter topology is first simulated on MATLAB and then a prototype has been designed in order to verify the simulation and experimental results. Finally the simulation and experimental results are found to be satisfactory. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1856